Conservation of migration area by transport cross sections using Cumulative Migration Method in deterministic heterogeneous reactor transport analysis. (September 2020) - Liu, Zhaoyuan; Giudicelli, Guillaume; Smith, Kord; Forget, Benoit
Abstract: Transport corrections are often used to account for the anisotropy in neutron scattering in multi-group deterministic simulations of light water reactors. It remains an open question on how to generate accurate transport cross sections using Monte Carlo codes and how to effectively evaluate the accuracy of existing transport correction methods. The anisotropy of neutron scattering with hydrogen in water has a large impact on neutron migration area, which is one important metric to be preserved. Recent work on the Cumulative Migration Method (CMM) has demonstrated that accurate homogenized transport cross sections and diffusion coefficients can be generated by conserving energy-dependent migration area. In this paper, a new transport correction method for computing heterogeneous transport cross sections based on CMM is proposed and verified on practical problems such as the B&W 1484 and the BEAVRS benchmark problems. Results demonstrate that CMM generated transport cross sections improve k e f f and the power distribution. Additionally, this paper demonstrates that CMM generated transport cross sections truly preserve the neutron migration area in deterministic calculations. Graphical abstract: Image 1 Highlights: A new transport correction method for computing heterogeneous transport XS based on CMM is proposed in this paper. The accuracy of full-core deterministic calculations using transport XS from CMM outperforms other methods in comparison. Transport XS generated using CMM truly preserves the neutron migration area in deterministic calculations.